Langkah Strategis Implementasi Aplikasi Layanan Interaktif di Perpustakaan - Mariani Mariani; Indira Irawati (Media Pustakawan, 2021)
Research on interactive service applications in libraries is still mostly about the use of various applications, application development, and evaluation of service applications in libraries. Utilization of service applications places more emphasis on the technology used, including assessing technical opportunities and obstacles. No research has been found that specifically discusses the preparation and management of interactive applications in libraries. The purpose of this study is to provide an overview of the application of interactive service applications that are mostly carried out in libraries and to open opportunities to obtain other views on the implementation of interactive service applications in libraries. This study uses a qualitative method with a literature review approach. From 20 articles, three major issues are found. They are the use of library service applications, a total of twelve articles; library service application development is found in 5 articles; and evaluation of library service applications in 3 articles. Conclusion from this research is that another view is needed in the implementation of interactive service applications in the library.